2010
DOI: 10.1371/journal.pone.0009415
|View full text |Cite
|
Sign up to set email alerts
|

SPARC Deficiency Results in Improved Surgical Survival in a Novel Mouse Model of Glaucoma Filtration Surgery

Abstract: Glaucoma is a disease frequently associated with elevated intraocular pressure that can be alleviated by filtration surgery. However, the post-operative subconjunctival scarring response which blocks filtration efficiency is a major hurdle to the achievement of long-term surgical success. Current application of anti-proliferatives to modulate the scarring response is not ideal as these often give rise to sight-threatening complications. SPARC (secreted protein, acidic and rich in cysteine) is a matricellular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 53 publications
(100 citation statements)
references
References 44 publications
6
92
1
1
Order By: Relevance
“…112 It distributes throughout the TM and it has been considered to have an important role in IOP regulation. 113 SPARC has also been detected in the iris of POAG patients, 114 while Seet et al 115 have found that SPARC deficiency in mice resulted in improved surgical survival in a mouse model of glaucoma filtration surgery. Aroca-Aguilar et al 116 reported an interaction between recombinant MYOC and SPARC.…”
Section: Wdr36 At the Glc1g Locusmentioning
confidence: 99%
“…112 It distributes throughout the TM and it has been considered to have an important role in IOP regulation. 113 SPARC has also been detected in the iris of POAG patients, 114 while Seet et al 115 have found that SPARC deficiency in mice resulted in improved surgical survival in a mouse model of glaucoma filtration surgery. Aroca-Aguilar et al 116 reported an interaction between recombinant MYOC and SPARC.…”
Section: Wdr36 At the Glc1g Locusmentioning
confidence: 99%
“…We have developed a mouse model of GFS which can be employed to investigate the postoperative subconjunctival scarring response (21). To ascertain that the murine model is relevant to the clinical setting, we applied MMC in the mouse model and examined the postoperative surgical responses.…”
Section: Validation Of the Glaucoma Filtration Surgical Mouse Model Fmentioning
confidence: 99%
“…Careful slit lamp, anterior segmentoptical coherence tomography (AS-OCT) and in vivo confocal microscopic examinations on subconjunctival blebs were performed at postoperative day 2, and weekly thereafter for a total of 4 wks as described previously (21). A bleb was judged to have failed if the surgical site appeared flat by slit lamp analysis.…”
Section: Detection and Analysis Of Blebsmentioning
confidence: 99%
See 2 more Smart Citations